2022
DOI: 10.1002/smll.202201036
|View full text |Cite
|
Sign up to set email alerts
|

Generation of Complex Tunable Multispectral Signatures with Reconfigurable Protein‐Based, Plasmonic‐Photonic Crystal Hybrid Nanostructures

Abstract: Structurally colored materials, which rely on the interaction between visible light and nanostructures, produce brilliant color displays through fine control of light interference, diffraction, scattering, or absorption. Rationally combining different color‐selective functions into a single form offers a powerful strategy to create programmable optical functions which are otherwise difficult, if not impossible to obtain. By leveraging structural protein templates, specifically silk fibroin, nanostructured mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 57 publications
0
12
0
Order By: Relevance
“…The two-color modes can be switched by the orientational control of the Janus microspheres using an external electric field . Omenetto et al also reported plasmonic–photonic crystal hybrid nanostructures by depositing gold on a silk inverse opal, producing versatile optical properties by manipulating the interplay between photonic bandgap and surface plasmonic resonance . It is believed that incorporating active structural manipulation into such plasmonic photonic crystals will further enable the convenient and dynamic tuning of the two structural coloring mechanisms, resulting in novel optical materials with more exciting applications.…”
mentioning
confidence: 99%
“…The two-color modes can be switched by the orientational control of the Janus microspheres using an external electric field . Omenetto et al also reported plasmonic–photonic crystal hybrid nanostructures by depositing gold on a silk inverse opal, producing versatile optical properties by manipulating the interplay between photonic bandgap and surface plasmonic resonance . It is believed that incorporating active structural manipulation into such plasmonic photonic crystals will further enable the convenient and dynamic tuning of the two structural coloring mechanisms, resulting in novel optical materials with more exciting applications.…”
mentioning
confidence: 99%
“…Optical multiplexing technology, which exploits the spatial characteristics of light, such as angle, amplitude, phase, and polarization, as distinct information channels to encode independent information, has emerged as a compelling approach for achieving color image transformation. Wang et al [75] recently demonstrated that angle-induced reversible pattern switching could be accomplished by creating silk photonic films featuring asymmetric multicolor patterns. The photonic film was generated by integrating surface plasmon resonance (SPR) and PBG effects in a single material.…”
Section: Phototunable Silksmentioning
confidence: 99%
“…By tuning the lattice constant or refractive index, full spectral ranged reflected colors are easily achieved on a responsive photonic crystal film. Such a stimuli-sensitive photonic crystal has been widely used in structure color display, , chemical and physical colorimetric sensor, anti-counterfeiting, , encryption, , and green printing. It is worth noting that rewritable photonic crystal paper as a kind of green printing material, in which the structural colored pattern can be reversibly printing and erase under external stimuli, has recently become prevalent, since paper is still the most important media for mankind to record information and spread the civilization. Moreover, photonic crystal paper with dye free character is more durable than traditional pigments and dyes, which can lessen the heavy environmental burden brought about by traditional paper industry.…”
Section: Introductionmentioning
confidence: 99%